(untitled) (Research, Society and Development, 2022)
Water monitoring is essential for water resources management and planning. In this sense, the objective of the work was to present the hydrological regime of permanence in the stations of Marabá and Parauapebas, as well as to estimate the water availability of the (SRHI) statistically through the SisCAH 1.0 program, the reference flows Q95 and Q90 for withdrawal of grants. The information from the fluviometric stations were collected through the National Hydrometeorological Network of the National Water Agency - ANA, obtained from the Hidroweb portal, due to the lack of stations in the (SRHI) only 2 fluviometric stations were selected with a series of data of, at least 10 years, being (29070100) and (29100000). Therefore, based on the state legislation of the State of Pará, the grantable flow recorded by the permanence curve at the stations studied was 29.668 (m3/s) in the Itacaiúnas tributary and 2.525 (m3/s) in the Parauapebas river, so activities and projects of engineering projects developed around the region must comply with the mentioned values ​​for the capture and use of the water body during the installation and/or operation of the enterprise, for the purpose of complying with regulations and water planning.